ANALYSING FACTORS THAT DRIVE CUSTOMERS PURCHASE INTENTION OF LICENSED TEAM MERCHANDISE SPORTS STATION MANADO - Titah, Vincent .; Lapian, S.L.H.V Joyce; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract:Â The success of a football club will not be separated from the role of fanatical fans who have always supported in each of their matches Whatever type of items associated with the club favourites would definitely be collected one of them soccer jersey t-shirt, Teams now try to direct their customers through the stores in which they market team related products, author interest to explore the condition that drive the customers purchase intention of the sport product in sports station Manado. This research Analysing Factors That Drive Customers Purchase Intention of Licensed Team Merchandise Sports Station Manado with 100 respondents are contributed and the Factor Analysis method is used in this research. There are four main findings in this research, which are: The first conclude component in this research is Brands; The second conclude component in this research is the Customer Loyalty; The Third conclude component in this research is Perceived Relative Price; The last conclude component in this research is Atmosphere. There are also nine recommendations that can be drawn in this research, which are, Product Variety, Product Quality, Product Packaging, Satisfaction, Trust, Habit, Perceived Quality, Perceived Value.Â Keywords: purchase intention, licensed team merchandise, sports, factor analysis